HUBUNGAN KEBERADAAN JENTIK NYAMUK DAN PERILAKU PEMBERANTASAN SARANG NYAMUK DEMAM BERDARAH DENGUE (PSN-DBD) MASYARAKAT DI DAERAH ENDEMIS DAN NON ENDEMIS KECAMATAN NANGGULAN KABUPATEN KULON PROGO - Arif Budiman (Universitas Airlangga, 2016)
Dengue fever occurrences are still problematic in Nanggulan district, Kulon Progo regency, which is in each year, the number of cases varies in each village. This research used ‘cross sectional’ design which samples of this research were taken from all the houses in Wijimulyo village as endemic village, and Banyuroto village as non-endemic village. The number of samples used in this research of 94 respondents. The instrument that used in obtaining data were questionnaires and observation check list. The result of Chi Square test in endemic village with influential factor dengue mosquito brending eradication was respondent attitude (p = 0,009) Contingency coefficient (p = 0,391), corelation is adequate, and action (p = 0,009) contingency coeficcient (p = 0,391) corelation is adequate . The result of Chi Square test in non endemic village with influential factor mosquito brending eradication was action (p = 0,011) Contingency coefficient (p = 0,422) corelation is adequate and action (p = 0,040) Contingency coefficient (p = 0,365) corealtion is adeqaute and it is found the fact that it’s better in non endemic village than in endemic village. Variable which influenced respondent attitude and existance of wiggler were not draining the tub over a week, used bucket, used can, used tire, not covering the tub, having fishless fond, so that the public health departement through Puskesmas suggest to conduct counseling of dengue mosquito breeding eridication, fond village monitoring by village officer and health officer to be drained in harvest season until planting season, changing permanent tub with impermanent one or big bucket in order to be easy to be cleaned.Keywords:Dengue Fever, Mosquito Breedin